Prevalence of Corneal Astigmatism in Age Related Cataract Patient in a Tertiary Eye Hospital (Central Medical College Journal, 2023)
Background: To investigate the magnitude and pattern of pre-existing corneal astigmatism in age related cataract patient.Method: This prospective observational study was carried out in a tertiary eye hospital from January 2020 to June 2020. We examined 577 eyes of 532 patients who underwent cataract surgery. The mean age at the time of surgery was 61.2 ±7.1 (40 to 100) years. Corneal astigmatism was measured with Auto Refracto Keratometer at least two times for each patient. Astigmatism was calculated from dioptric difference of vertical reading from horizontal reading. With the rule (WTR) astigmatism was considered when steep meridian at 900±200. Against the rule (ATR) astigmatism was considered when steep meridian at 1800±200. Astigmatism is in other direction is defined as oblique.Result: The pattern of astigmatism was ATR astigmatism in 237 eyes (41%), WTR astigmatism in 165 eyes (28.6%) and Oblique in 175 eyes (30.4%). Prevalence of ATR astigmatism was more than WTR astigmatism and prevalence of ATR astigmatism axis significantly increased with the increase in age. Average corneal power was 45.23D. Corneal astigmatism was 0.0D to 0.5D in 274 eyes (47.5%), 0.51D to 1.0D in 175 eyes (30.3%), 1.01D to 2.0D in 98 eyes (17.0%) and more than 2D in 30 eyes (5.2%) cases. Corneal astigmatism of most cataract surgery candidates fell between 0.50D to 1.50 D in 360 eyes (62.4%) cases.Conclusion: Thirty five percent (35%) pre-operative patient had 1D or more corneal astigmatism and sixty five percent (65%) had less than 1Dcorneal astigmatism.Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 67-70